Evaporation of nanofluid drop - Mak, Chien Yee (2015)
Nanofluid is highly favoured and useful in many applications for various industries. The purpose of this research is to investigate the evaporation and nanoparticles flow in binary base nanofluid. Multi Walled Nanotubes (MWNTS), Aluminum Oxide (Al2O3) and Fluorescent Particles (NPs) nanoparticles were mixed with increasing of ethanol concentrations in all evaporation experiment. Results show that the evaporation process consists of chaotic, stabilised and evaporated period with the presence of ethanol. The evaporation rate is greatly reduced as the ethanol concentration increases from 10% to 40% and/or 50%. It also formed eddy current with stronger vorticity at the preliminary stage of evaporation. In Al2O3 experiments, the evaporation rate decreased with increase of particle concentration. Findings demonstrate that the particle mass and ethanol directly affects the aggregation of particles within the droplet. More particle aggregations were observed with the increase of either particle mass or ethanol concentration. Particle motion was observed and a flow analysis was conducted using PIV software for NPs nanofluid. It proves that particles were moving in 2 directions – towards boundary and center of the droplet. The particles towards boundary will affect the thickness of coffee ring. The overall flow transition is in circular motion with “pull and attract” forces during evaporation. In conclusion, there are pros and cons for using binary base fluid. It can affect the factors of evaporation and necessary to adjust correctly. Further investigation should be conducted with the addition of surfactant into the binary base nanofluid to understand the flow analysis better.